Exploring Smartphone Usage as an ICT Tool among College Students of Chaturbhujeshwar Janata Multiple Campus - Shrestha, Laxman (Chaturbhujeshwar Academic Journal, 2023)
This study aims to reveal students' and lecturers' perspectives on Information and Communication Technology (ICT), including its pros and cons, and to cultivate a technology-friendly environment in colleges. It extensively examines the potential benefits and challenges linked to integrating Mobile Technology in education. Moreover, the research seeks to understand how both students and educators perceive mobile technology use among college students, evaluating its advantages and disadvantages. This study employs the Connectivism theory as the analytical framework to evaluate the study's outcomes. Data analysis involves the utilization of frequency analysis. The research design is characterized as a concurrent mixed methods approach. The primary research instruments utilized encompass a semi-structured questionnaire and an interview checklist. The target population consists of 700 students and 22 teaching faculties enrolled in Bachelor's degree programs, with 152 students and all 22 faculties selected as respondents. Upon the comprehensive integration and synthesis of data, a total of 14 fundamental themes and two overarching perception themes were discerned through the analysis process. The findings reveal that smart phones are widely used among college students for studying, communication, and accessing information. Meanwhile, students and lecturers have acknowledged both the benefits and the potential negative impacts on academic performance. The study provides valuable insights into the perceptions and experiences of students and educators regarding the usage of mobile technology in education. As technology continues to play a vital role in education, it is essential to foster a conducive learning environment by leveraging its advantages while mitigating its potential drawbacks.